Prevalence of jumping and landing techniques in volleyball: An analysis of elite female players - Tillman, M. D.; Hass, C. J.; Brunt, D.; Miller, J. (2001)
All tests were statistically significant (P<0.001). The majority (86.5%) of offensive jumps were performed using both feet. Most (50%) offensive landings occurred with both feet, but 38.9% resulted in a left foot first landing, while 11.1% utilized a right foot first technique. Over 98% of defensive jumps used both feet. Defensive landings involving both feet were most prevalent (47.2%) followed by right foot landings (36.0%) and left foot landings (16.8%). The distribution of jumps and landings appears in Table 1. The overwhelming majority of propulsive jumps (offensive and defensive) are performed using both feet. Jumping with both feet provides a wide base of support resulting in stable force production and allowing the forces to be generated by both limbs for maximal vertical performance. Although more landings are made with two feet than with one, the relative frequencies for landing are far more variable than for the jump phase. Approximately half of all landings in volleyball utilize only the right or left foot. Accordingly, the most frequent mechanism of knee injury in volleyball is landing from a jump (Ferretti, et al., 1992). The relatively high number of asymmetric footfalls during landing may lead to loss of balance and subsequent injury. Interestingly, 62.5% of right foot jumps result in right foot landings and 59.4% of left jumps end in left foot landings. Additionally, most jumps are made with two legs, but half of the associated landings are made with only one leg. Thus a single leg must dissipate the forces originally created by both legs. This situation could be quite detrimental. SUMMARY Volleyball is a high-risk sport relative to the knee joint and landing techniques appear to be quite variable. Further kinematic and kinetic analyses of these different landing techniques are required to fully quantify the biomechanical risks of performing these tasks.